1998
DOI: 10.1128/mcb.18.7.3668
|View full text |Cite
|
Sign up to set email alerts
|

Role of Histone H1 as an Architectural Determinant of Chromatin Structure and as a Specific Repressor of Transcription onXenopus Oocyte 5S rRNA Genes

Abstract: We explore the role of histone H1 as a DNA sequence-dependent architectural determinant of chromatin structure and of transcriptional activity in chromatin. The Xenopus laevis oocyte-and somatic-type 5S rRNA genes are differentially transcribed in embryonic chromosomes in vivo depending on the incorporation of somatic histone H1 into chromatin. We establish that this effect can be reconstructed at the level of a single nucleosome. H1 selectively represses oocyte-type 5S rRNA genes by directing the stable posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 131 publications
5
69
0
1
Order By: Relevance
“…Under the experimental conditions used by us, no evidence could be found for asymmetric protection of linker DNA as has been observed with Xenopus 5 S rDNA (25,62,63). Interestingly this chromatosome position in Xenopus 5 S rRNA has been found more recently to be susceptible to sequence-specific artifacts, and another major chromatosome position that involves protection of 20 bp on one side of the nucleosome has also been reported (24,64,65). If this type of protection were the case here, it implies that the incorporation of histone H1 led to a shift in the equilibrium position of nucleosomes from position A to position B. Alternatively, since nucleosomes are more mobile in the absence of linker histones (66), it is possible that digestion with micrococcal nuclease could induce short range sliding of nucleosomes.…”
Section: Histone H1 Equally Affects the Positioning Of The Histone Ocmentioning
confidence: 80%
“…Under the experimental conditions used by us, no evidence could be found for asymmetric protection of linker DNA as has been observed with Xenopus 5 S rDNA (25,62,63). Interestingly this chromatosome position in Xenopus 5 S rRNA has been found more recently to be susceptible to sequence-specific artifacts, and another major chromatosome position that involves protection of 20 bp on one side of the nucleosome has also been reported (24,64,65). If this type of protection were the case here, it implies that the incorporation of histone H1 led to a shift in the equilibrium position of nucleosomes from position A to position B. Alternatively, since nucleosomes are more mobile in the absence of linker histones (66), it is possible that digestion with micrococcal nuclease could induce short range sliding of nucleosomes.…”
Section: Histone H1 Equally Affects the Positioning Of The Histone Ocmentioning
confidence: 80%
“…Also, it has been shown that the histone H1-mediated repression of oocyte-type 5S rRNA genes is dependent upon the binding of histone H1 to the AT-rich flanking sequences of these genes (19,39). More recent work suggests that the specific transcriptional repressor effect of histone H1 on the Xenopus oocyte 5S rRNA gene is linked to the presence of an AT-rich sequence 3Ј to the gene as well as to the binding of histone H1 to the 3Ј end of the nucleosome core, blocking the access to a key promoter element (33). For Xenopus embryos, Vermaak et al have described the globular domain of histone H1 as being sufficient to direct this specific gene repression (40).…”
Section: Discussionmentioning
confidence: 99%
“…Distamycin has been described as a drug that can specifically displace histone H1 from oligo(dA) ⅐ oligo(dT) runs (17,33). In the case of the wild-type muIFN-␤ promoter integrated into chromatin, distamycin was able to activate the promoter after virus infection but only if the promoter carried the upstream AT-rich region (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(24,25,45,(47)(48)(49)(50)), suggesting that mammalian body temperature might promote some level of nucleosome redistribution in vivo. Thermal repositioning is most rapid at high temperatures (up to 65°C) and in the absence of divalent cations or linker histones (45,48,51,52)). In general, thermal repositioning appears to result in redistribution between sites that are all at least moderately-favored during nucleosome assembly (causing increases in some moderately favored positions and decreases in some strongly favored positions).…”
Section: Hswi/snf-favored Positions Differ From Thermally Favored Posmentioning
confidence: 99%